The Role of Auditor in Sustainability Reporting - Annisa Auliani; Desinta Pramesti; Lidia Yunita (LAFADZ JAYA Publisher, 2023)
The publication of sustainability reporting has become a trend in Indonesia even though the regulations for publishing sustainability reporting have not been mandated. Some companies have published their sustainability reports voluntarily as a demand for the company’s transparency for its operations to stakeholders. To ensure that the sustainability report submitted by the company follows the guideline, the role of an auditor is needed to carry out the assurance. Therefore, the approach used in this study is qualitative. The qualitative method is research that uses descriptive data from the observation of secondary data. Secondary Data is information that already exists from before and is a collection of data by researchers to complement the data needed for research. In this study, the audit of sustainability reports can increase the credibility and accuracy of the information, primarily to support decision-making for stakeholders; this study tries to explain the role of auditors in sustainability reports.